2022
DOI: 10.1002/hyp.14681
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of snowpack structure in gaps and under the canopy in a humid boreal forest

Abstract: The boreal forest covers a significant portion of the Northern Hemisphere and is snow-covered for over half of the year. Understanding the interactions between the forest canopy and snow is essential in hydrological, meteorological, and climate modelling. However, this is challenging because the density of a forest can range from closed canopies to open gaps. In winter 2018-2019, we assessed differences in snowpack microstructure in small forest gaps and under the canopy of a humid boreal site in eastern Canad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 68 publications
2
16
0
Order By: Relevance
“…This may affect (1) the location of the regional snowline (as calculated using fSCA here) and (2) the TWI during ROS inferred from snow pillows ( 76 ). Relatively broader forest cover therefore suggests actual snowpack losses across watersheds may be lower (reducing the snowpack contribution to TWI) ( 74 , 77 ) than what may be implied by in-situ SWE losses. This is supported by our modeling results that account for canopy–snow interactions, indicating lower snowmelt contributions to TWI in the 6F ROS event.…”
Section: Snow As a Passive Conduit For Rainfallmentioning
confidence: 99%
See 1 more Smart Citation
“…This may affect (1) the location of the regional snowline (as calculated using fSCA here) and (2) the TWI during ROS inferred from snow pillows ( 76 ). Relatively broader forest cover therefore suggests actual snowpack losses across watersheds may be lower (reducing the snowpack contribution to TWI) ( 74 , 77 ) than what may be implied by in-situ SWE losses. This is supported by our modeling results that account for canopy–snow interactions, indicating lower snowmelt contributions to TWI in the 6F ROS event.…”
Section: Snow As a Passive Conduit For Rainfallmentioning
confidence: 99%
“…However, ground and satellite observations are partial to exposed, flat terrain. Vegetation tends to collect less snowpack in-stand compared to exposed areas ( 73 , 74 ), yet it can shelter snow from wind-driven turbulent heat exchange, potentially lowering TWI during ROS ( 12 , 17 , 75 ). Beneath-canopy SWE and its in-storm changes are invisible to both satellites and snow pillows.…”
Section: Snow As a Passive Conduit For Rainfallmentioning
confidence: 99%
“…While available observations did not allow to evaluate our simulations in more detail, our findings are generally consistent with the few observational studies that have addressed snow microstructural properties, stratigraphy, and its spatial variability within the forest. Comparing snow pits in canopy gaps and closed canopy, Bouchard et al (2022) identified layers specific to closed-canopy locations that were absent in forest gaps. Optical grain size measurements in trenches along tree boles presented by Molotch et al (2016) revealed distinct differences in snow grain size at small vs. large distance from tree trunks, and faster metamorphism at south-vs. north-exposed sides of trees.…”
Section: New Insights On the Impact Of Canopy Structure On Snow Strat...mentioning
confidence: 99%
“…A modelling system that combines both, the most complex snow and canopy representation, is lacking to date. At the same time, a few observational studies have provided evidence that tree-scale processes do impact layer-scale snowpack properties (Bouchard et al, 2022;Teich et al, 2019;Molotch et al, 2016). These observations document, for example, different microstructural properties under trees, in the unloading zone, and in canopy gaps.…”
mentioning
confidence: 99%
“…A thin snowpack below the canopy favors the diffusion of water vapor among snow layers, leading to gradient metamorphism and grain growth (Colbeck, 1983). Larger grains increase the hydraulic conductivity of the snowpack (Bouchard et al, 2022). Canopy snow unloading, meltwater dripping, and accumulation of vegetation debris enhance the sub-canopy snowpack heterogeneity, thereby increasing the likelihood of preferential flow under the trees and the formation of melt-freeze layers (Bründl et al, 1999;Teich et al, 2019;Bouchard et al, 2022).…”
Section: Introductionmentioning
confidence: 99%